Push and pull factors of suburban local youth towards career in oil palm plantation - Mohamad Amizi Ayob; Norehan Abdullah; Siti Aznor; Zul Ariff Abdul Latiff (2016)
The rapid expansion of oil palm plantation in Malaysia in 1990, 2.03 million hectares to 5.39 million hectares in 2014 (Malaysia Palm Oil Board 2015) caused required high labour intensive in this sector. More than 78% of labor (Azman 2014) in this sectors mainly came from Indonesia, Bangladesh and Philippines. Malaysia has become the main attention for the foreign labours to work in this country due to the wages more competitive and generative working condition especially the plantation sector provide the conducive accommodation compared to their origin country. The pressing issue now is the rising social issues of the illegal foreign workers and influx of the foreign workers without work permit. One of the best solutions is hire the local youth to works in oil palm plantation. The main problem is compounded by the fact that it is difficult to hire the local youth workers due to the migration of local youth from government settlers scheme oil palm plantation located in the sub urban area. As a result this scheme area dominated with foreign labour. This study which was conducted in the State of Johore wants to find the push and pull factors\towards the career in oil palm plantation which involved the repulsion, inclination and attraction based on their perceptions .A survey method through questionnaire was used to collect data from 278 of local youth between 16 years to 40 years old as focused respondents which were selected using random sampling method. Descriptive analysis was applied based on their demographic factors and the involvement of the local youth in oil palm plantation.